ASSESS THE PREVALENCE OF HYPERTENSION AND KNOWLEDGE REGARDING THE PREVENTION OF STROKE - MISSRIYA MA, SAHBANATHUL; John, Johncey (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Hypertension is the most crucial and common health problem in developed and undeveloped countries. Although hypertension is a treatable condition, without treatment, it leads to serious and life-threatening complications such as heart, kidney, and brain disorders. Prevention plays a major role in controlling the disease, which can be achieved by increasing the knowledge through awareness of the public and changing their attitude and practice. The study was aimed to assess the prevalence of hypertension, assess the knowledge regarding prevention of stroke among people with hypertension and to associate the knowledge regarding prevention of stroke with selected demographic variables of people. Methods: Descriptive design was adopted. Using simple random sampling technique, 60 samples were selected. The data were collected, analyzed in terms of both inferential and descriptive statistics. Results: The study result showed that among the total number of people (1248) surveyed, 476 (38.1%) were prevalent in hypertension. Among the randomly selected 60 people with hypertension, 47 (78.3%) patients had inadequate knowledge, 13 (21.7%) had moderate knowledge, and none of them had adequate knowledge regarding prevention of stroke. Most people residing at Kottayam had poor knowledge on hypertension and prevention of stroke. Conclusion: The study concluded that though there was more prevalence of hypertension and most of them had inadequate knowledge on prevention of stroke and there is a need to make the people aware about the complications of hypertension and prevention aspects.